Ćwiczenie ekologicznej wyobraźni. O poezji Julii Fiedorczuk - Węgrzyniak, Anna (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The key to reading Julia Fiedorczuk’s poems – interpreted within the paradigm of eco-poetry – are the words used in the titles of her poetry volumes: “bio”, “planet” and “oxygen”, which foretell bio-centrism. The poetic imagery unites organic tissues with the artist’s “texture”. A love relationship of a human with a non-human reveals ecological sensitivity, yet it is a painful “love” because it is accompanied by the disagreement about the fragility of existence and the progressing degradation of the planet.